miR-29b-3p Increases Radiosensitivity in Stemness Cancer Cells via Modulating Oncogenes Axis - Pan, Dong; Du, Yarong; Li, Rong; Shen, Aihua; Liu, Xiaodong; Li, Chuanyuan; Hu, Burong (Frontiers in Cell and Developmental Biology, 2021)
Radioresistance conferred by cancer stem cells (CSCs) is the principal cause of failure of cancer radiotherapy. Eradication of CSCs is a prime therapeutic target and a requirement for effective radiotherapy. Three dimensional (3D) cell cultured model could mimic the morphology of cells in vivo and induce CSCs properties. Emerging evidence suggests that microRNAs (miRNAs) play crucial roles in the regulation of radiosensitivity in cancers. In this study, we aim to investigate the effects of miRNAs on radiosensitivity of 3D cultured stem-like cells. Using MiRNA microarray analysis in 2D and 3D cell culture models, we found that the expression of miR-29b-3p was down-regulated in 3D cultured A549 and MCF7 cells compared to monolayer (2D) cells. Clinic data analysis from TCGA database exhibited that miR-29b-3p high expression showed significant advantages in LUAD and BRCA patients’ prognosis. The subsequent experiments proved that miR-29b-3p overexpression decreased the radioresistance of cells in 3D culture and tumors in vivo through interfering kinetics process of DNA damage repair and inhibiting oncogenes PIK3R1, AKT2, and Bcl-2 In addition, miR-29b-3p knockdown enhanced cancer cells invasion and migration capability. MiR-29b-3p overexpression decreased the stemness of 3D cultured cells. In conclusion, our results demonstrate that miR-29b-3p could be a sensitizer of radiation killing in CSC-like cells via inhibiting oncogenes expression. MiR-29b-3p could be a novel therapeutic candidate target for radiotherapy.